Primate dietary ecology in the context of food mechanical properties. Issue 98 (September 2016) - Coiner-Collier, Susan; Scott, Robert S.; Chalk-Wilayto, Janine; Cheyne, Susan M.; Constantino, Paul; Dominy, Nathaniel J.; Elgart, Alison A.; Glowacka, Halszka; Loyola, Laura C.; Ossi-Lupo, Kerry; Raguet-Schofield, Melissa; Talebi, Mauricio G.; et al.
Abstract: Substantial variation exists in the mechanical properties of foods consumed by primate species. This variation is known to influence food selection and ingestion among non-human primates, yet no large-scale comparative study has examined the relationships between food mechanical properties and feeding strategies. Here, we present comparative data on the Young's modulus and fracture toughness of natural foods in the diets of 31 primate species. We use these data to examine the relationships between food mechanical properties and dietary quality, body mass, and feeding time. We also examine the relationship between food mechanical properties and categorical concepts of diet that are often used to infer food mechanical properties. We found that traditional dietary categories, such as folivory and frugivory, did not faithfully track food mechanical properties. Additionally, our estimate of dietary quality was not significantly correlated with either toughness or Young's modulus. We found a complex relationship among food mechanical properties, body mass, and feeding time, with a potential interaction between median toughness and body mass. The relationship between mean toughness and feeding time is straightforward: feeding time increases as toughness increases. However, when considering median toughness, the relationship with feeding time may depend upon body mass, such that smaller primates increase their feeding time in response to an increase in median dietary toughness, whereas larger primates may feed for shorter periods of time as toughness increases. Our results emphasize the need for additional studies quantifying the mechanical and chemical properties of primate diets so that they may be meaningfully compared to research on feeding behavior and jaw morphology.